Comparison of the Effectiveness of Related Functions in Web of Science and Scopus - Char, Dorothy C.P.; Ajiferuke, Isola (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This study compares the related functions in Web of Science and Scopus. The results indicate no significance difference in the effectiveness of the related functions by references of the two systems; within Scopus, the related function by references was found to be more effective than those by authors and keywords. Analyse comparative des fonctions similaires de Web of Science et de Scopus. Les résultats ne témoignent d'aucune différence significative dans l'efficacité des fonctions similaires des deux systèmes pour les références. Dans Scopus, la fonction similaire pour les références était plus efficaces que celles pour les auteurs ou pour les mots-clés.